Physiological studies on fainting due to shime waza (choking) - Nimura, Y.; Higaki, E.; Motohashi, H.; Yokoyama, Y. (The Arts and Sciences of Judo, 2022)
Judo is unique among the Olympic sports because shime-waza (choking) is allowed to subdue an opponent in competition. However, safety of shime waza has been discussed for over the last half century. Published physiological studies on human experiments of strangulation or shime-waza were reviewed to investigate the safety and mechanism of fainting due to shime-waza. The first human experiment of acute arrest of cerebral circulation was performed in 1943 to investigate the physiological changes during fainting. An average time from cervical compression to loss of consciousness was 6.8 seconds and that from unconsciousness to revival was 4 - 8 seconds. Physiological studies on fainting due to shime-waza have been reported since 1950 by Japanese sports scientists followed by western doctors. Kata juji jime (half cross strangle) was mainly used for black belt judoka. It took about 6 - 10 seconds to fall unconscious and 7 - 12 seconds to revive from unconsciousness. Many subjects developed anoxic convulsion after fainting. As there were no significant changes in heart rate and blood pressure during the experiment, the most important mechanism causing unconsciousness was suggested to be brain ischemia due to decreased cerebral blood flow by carotid artery compression and carotid sinus reflex (CSR) contributes little to the response to shime-waza. Human experiments of shime waza have not developed any dangerous effect. The cause of fainting was not CSR but brain hypoxia due to decreased cerebral blood flow by carotid artery compression.